2004
DOI: 10.5123/s1679-49742004000200002
|View full text |Cite
|
Sign up to set email alerts
|

Oocistos de Cryptosporidium e cistos de Giardia: circulação no ambiente e riscos à saúde humana

Abstract: Cryptosporidium Oocysts and Giardia Cysts: Environmental Circulation and Health RisksOocistos de Cryptosporidium e cistos de Giardia: circulação no ambiente e riscos à saúde humana* ResumoEmbora a presença de protozoários em águas para consumo humano revele-se como um importante problema de Saúde Pública em diversos países, o conhecimento sobre esses riscos, no Brasil, ainda é escasso. Em vista dessa lacuna, apresentamse, neste trabalho, informações que ajudam a compor e explicar a circulação no ambiente e a i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
21

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 14 publications
0
15
0
21
Order By: Relevance
“…However, some researchers 13,14 have demonstrated that even these sources of water can become contaminated. Bastos et al 13 and Heller et al 14 emphasized the possibility of contamination of water treatment plants with cysts of G. duodenalis and Cryptosporidium parvum due to technical problems involving coagulation, filtration, or disinfection.…”
Section: Risk Factors Categories or (95%ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers 13,14 have demonstrated that even these sources of water can become contaminated. Bastos et al 13 and Heller et al 14 emphasized the possibility of contamination of water treatment plants with cysts of G. duodenalis and Cryptosporidium parvum due to technical problems involving coagulation, filtration, or disinfection.…”
Section: Risk Factors Categories or (95%ci)mentioning
confidence: 99%
“…However, some researchers 13,14 have demonstrated that even these sources of water can become contaminated. Bastos et al 13 and Heller et al 14 emphasized the possibility of contamination of water treatment plants with cysts of G. duodenalis and Cryptosporidium parvum due to technical problems involving coagulation, filtration, or disinfection. Although treated water supplied by public services may not be 100% contamination-free, the expected protective effect against G. duodenalis was verified in the present study in comparison with the use of water obtained from wells or natural springs.…”
Section: Risk Factors Categories or (95%ci)mentioning
confidence: 99%
“…According to HELLER et al (2004) 10 , Cryptosporidium spp and Giardia spp are resistant to chlorinated water in the amount recommended by Brazilian Health Ministry.…”
Section: Discussionmentioning
confidence: 99%
“…A contaminação de oocistos de C. parvum e C. hominis em águas superficiais ou de abastecimento público assume um papel importante no comprometimento ambiental e na saúde pública (Carey et al 2004), haja visto que inúmeros casos já foram registrados em diferentes países (Fuente et al 1999, Laubach et al 2004, inclusive no Brasil (Baraldi et al 1999, Heller et al 2004.…”
Section: Repercussão Na Saúde Públicaunclassified